Pengaruh Kualitas Produk, Kualitas Layanan dan Persepsi Harga Terhadap Kepuasan Pelanggan Produk Smartphone Samsung di Bogor - Yanto Hermawan; Dina Maylani; Mumuh Mulyana (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The purpose of the research is to know the influence of product quality, service quality and perceived price on customer satisfaction (case study of smartphone Samsung in Bogor). this research used eksogen variable (product quality, service quality and perceived price) and endogen variable (customer satisfaction). This research used non probability sampling sample method and the total of respondents is 200, the respondents chosen were respondents who had used or were wearing smartphone Samsung. Research data was processed using SPSS AMOS 21. The result of this research is product quality has a positive and significant influence to customer satisfaction with CR (3,312 > 1,96) or P value (*** < 0,05), therefore hypothesis 1 was accepted. Service quality has a positive and significant influence to customer satisfaction with CR (2,750 > 1,96) or P value (0,006 < 0,05), therefore hypothesis 2 was accepted. Perceived price has a positive and significant influence to customer satisfaction with CR (2,076 > 1,96) or P value (0,004 < 0,05), therefore hypothesis 3 was accepted. Product quality, service quality and perceived price has a positive and significant influence on customer satisfaction with R Square value in the amount 0.841 or 84.1%, therefore hypothesis 4 was accepted. Keywords : product quality, service quality, perceived price, customer satisfaction